If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(r + 3) + -9r = -3r + -1(3r) + 8 Reorder the terms: -9(3 + r) + -9r = -3r + -1(3r) + 8 (3 * -9 + r * -9) + -9r = -3r + -1(3r) + 8 (-27 + -9r) + -9r = -3r + -1(3r) + 8 Combine like terms: -9r + -9r = -18r -27 + -18r = -3r + -1(3r) + 8 Remove parenthesis around (3r) -27 + -18r = -3r + -1 * 3r + 8 Multiply -1 * 3 -27 + -18r = -3r + -3r + 8 Reorder the terms: -27 + -18r = 8 + -3r + -3r Combine like terms: -3r + -3r = -6r -27 + -18r = 8 + -6r Solving -27 + -18r = 8 + -6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '6r' to each side of the equation. -27 + -18r + 6r = 8 + -6r + 6r Combine like terms: -18r + 6r = -12r -27 + -12r = 8 + -6r + 6r Combine like terms: -6r + 6r = 0 -27 + -12r = 8 + 0 -27 + -12r = 8 Add '27' to each side of the equation. -27 + 27 + -12r = 8 + 27 Combine like terms: -27 + 27 = 0 0 + -12r = 8 + 27 -12r = 8 + 27 Combine like terms: 8 + 27 = 35 -12r = 35 Divide each side by '-12'. r = -2.916666667 Simplifying r = -2.916666667
| 7y-1=2y+6-2 | | 81r^2-90r+25=0 | | 6x-8x=9+4x | | x-10(-8)=85 | | 8-10(-8)=85 | | 9-3(1-q)=7-4(2-q) | | 7=56n | | 9y-10(85+10y)=-122 | | 7.8-n=0.2 | | x-10y=85 | | x^4-5x^2+4=0 | | 6b+8=2b-8 | | n+25=18 | | 4x^5=24x^3 | | 9(2x+5)+3=26 | | 11x+5=-15+6x | | 18=x-7x | | 11x+5=-156x | | 36w^2+60w+25=0 | | t+17-2t=-3(t-1)-3 | | p^2-36=0 | | 2x^2+1=51 | | -2x+1=6x+9 | | x=-5y-5 | | 4x-3=-17 | | 4K(2K-7)= | | q=2n+2w | | 9q^2+12q+4=0 | | -7(p-3)+11=3p-12-p | | 3-7x=-3x-29 | | 3a+4=a+10 | | 5x+10=4x+12 |